2014
DOI: 10.1680/adcr.13.00051
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anhydrite proportion in a calcium sulfoaluminate cement and Portland cement blend

Abstract: Calcium sulfoaluminate (CSA) cement and ordinary Portland cement (OPC) blends are innovative binders. In comparison with OPC, these mixtures can reduce the environmental impact of cement production as well as increase the hardening speed. This article deals with the effects of calcium sulfate (anhydrite) percentage on hydration mechanisms, compressive strength and dimensional stability of binders containing 40% OPC. Calcium sulfate quantity is an essential parameter that can be used to control the hardening sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 9 publications
1
25
1
Order By: Relevance
“…The hydration mechanisms of the CSA–PC–C$ binder incorporate some aspects of the neat PC and neat CSA hydration, but not all, and also include new reactions unique to the ternary system. Figure 2 shows the chemical reactions from each component of the CSA–PC–C$ system 12,57–59 . Here, reaction pathways (routes 1, 2, 3, etc.)…”
Section: Hydrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydration mechanisms of the CSA–PC–C$ binder incorporate some aspects of the neat PC and neat CSA hydration, but not all, and also include new reactions unique to the ternary system. Figure 2 shows the chemical reactions from each component of the CSA–PC–C$ system 12,57–59 . Here, reaction pathways (routes 1, 2, 3, etc.)…”
Section: Hydrationmentioning
confidence: 99%
“…Binders that rapidly hydrate to form ettringite as the major hydration product (∼24 h) are commonly referred to as ettringite‐accelerated binders. Examples of ettringite‐accelerated binders in the literature include CSA–C$ (calcium sulfoaluminate cement with calcium sulfate), CSA–PC (calcium sulfoaluminate cement blended with Portland cement), CSA–C 2 S (calcium sulfoaluminate belite), CSA–PC–C$, CAC–PC–C$, CAC–C$ (calcium aluminate cement blended with calcium sulfate), and LSG (ladle slag and gypsum) 9–13 . Among these binders, blended types of cement composed of CSA–PC–C$ and CAC–PC–C$ have shown the potential for a wide range of applications and comprise materials that are already produced commercially.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, ye'elimite hydration proceeds through dissolution and precipitation [142], leading to the precipitation of various hydrates. In the presence of anhydrite (calcium sulfate), ye'elimite hydrates to form ettringite as well as gibbsite (Reaction R1') [18,107,143,144]:…”
Section: I41 Effect Of Amount and Nature Of The Added Calcium Sulfatementioning
confidence: 99%
“…In the absence of calcium sulfate, the hydration of ye'elimite can lead to the formation of monosulfoaluminate and gibbsite (Reaction R2') [18,107,143,144]:…”
Section: I41 Effect Of Amount and Nature Of The Added Calcium Sulfatementioning
confidence: 99%
“…By contrast, there was rather less effect on dimensional stability in ternary blends. Trauchessec [40] explored the effect of different anhydrite contents on the performance of ternary binders containing fixed OPC proportions and concluded that blends with 40% OPC, 46.5% CSA, and 13.5% anhydrite had optimal properties (in terms of strength and shrinkage).…”
Section: Introductionmentioning
confidence: 99%